Effectiveness of drill-based vocal technique instruction on high school students' singing ability - Multia Evarina; Syeilendra Syeilendra; Indrayuda Indrayuda; Jupriani Jupriani (Journal of Educational and Learning Studies, 2026)
Objective: This study aimed to examine the effectiveness of the drill method in improving the singing ability of Grade XI students during vocal technique instruction at SMAN 1 Situjuah Limo Nagari. Methods: A quantitative approach employing a quasi-experimental Nonequivalent Control Group Design was used. Forty-two students participated, comprising 21 students in the experimental group and 21 in the control group. Data were collected through pretest and posttest performance assessments and analyzed using the Wilcoxon Signed-Rank Test. Results: The experimental group's mean score increased from 65.4% to 83.5% (+18.1%), whereas the control group declined from 71.9% to 66.4% (−5.5%). Improvements were observed in breathing (+16.9%), intonation (+18.7%), articulation (+14.9%), and resonance (from 60.6% to 83.0%). Statistical analysis confirmed a significant improvement in the experimental group (p = 0.000) but not in the control group (p = 0.640). Conclusions: The drill method effectively enhances students' singing ability and vocal technique, providing an evidence-based instructional strategy for improving vocal learning in secondary school music education